2007
DOI: 10.1111/j.1365-4632.2007.03336.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of Demodex folliculorum in patients receiving phototherapy

Abstract: Background Patients with immunodeficiency are prone to infestation with Demodex folliculorum mites. Ultraviolet (UV) radiation can lead to immunosuppression and sebaceous gland hyperplasia. Although some cases of demodicidosis related to UV radiation exposure have been reported, no studies have been performed on the incidence of D. folliculorum and its clinical characteristics in patients receiving phototherapy. Objective To investigate the effects of phototherapy on the density of D. folliculorum infestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 26 publications
2
29
0
8
Order By: Relevance
“…2004). Because of immunosuppression, old age, topical and systemic corticosteroid usage, topical pimecrolimus and tacrolimus usage, and diabetes mellitus are predisposing factors for Demodex species incidence (Kulac et al 2008). The increased incidence of Demodex species in patients with hematological malignancies, acquired immunodeficiency syndrome (AIDS), and diabetes mellitus suggests that immunosuppression plays a major role (Akilov et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…2004). Because of immunosuppression, old age, topical and systemic corticosteroid usage, topical pimecrolimus and tacrolimus usage, and diabetes mellitus are predisposing factors for Demodex species incidence (Kulac et al 2008). The increased incidence of Demodex species in patients with hematological malignancies, acquired immunodeficiency syndrome (AIDS), and diabetes mellitus suggests that immunosuppression plays a major role (Akilov et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Rosaceiform dermatitis has been reported following repeated facial application of topical steroids and other immunomodulators with similarly increased numbers of mites recorded [13] . Several other studies have shown that Demodex mite numbers are increased in immunosuppressed patients, children with leukaemia receiving chemotherapy [14] , patients with HIV infection and AIDS [15,16] , patients undergoing phototherapy [17] and patients on chronic dialysis [18] .…”
mentioning
confidence: 99%
“…Ayrıca rosacea, steroidle indüklenen dermatit, primer irritasyon dermatiti, seboreik dermatit, folikülit ve kronik blefarit gibi deri hastalıklarının Demodex enfestasyonuyla ilişkili olduğu bildirilmiştir (6) . Bu parazitin patojen olup, olmadığı hâlen tartışma konusu olsa da birçok deri hastalığının etiyopatogenezinde bu parazitin rol aldığı, bağışıklığı azalmış ya da baskılan-mış olan hastalarda patojen olabileceği bildirilmiştir.…”
Section: Discussionunclassified
“…Kulaç ve ark. (6) çeşitli nedenlerle fototerapi alan 45 hasta ve 43 sağlıklı deneme grubunda Demodex sp. araştırması yapmış, fototerapi alan 45 hastanın 13'ünde (%28.9) ve sağlıklı grubun üçünde (%7) Demodex sp.…”
Section: Discussionunclassified